Моделювання та аналіз мімічних проявів емоцій - Кривонос, Ю.Г.; Крак, Ю.В.; Бармак, О.В.; Єфімов, Г.М. (Видавничий дім "Академперіодика" НАН України, 2008)
This work presents a computer technology for the emotion detection on human faces. The model is offered as a linear combination of some basic emotions. Parameters of the model are found with the help of the method of deformable templates using NURBS curves. An arbitrary emotion on a human face is detected as a convex combination of basic emotions.